Addition of levosimendan to overcome acute cardiogenic shock—Paving the way for later heart transplantation—A first case report. Issue 2 (19th December 2020) - Flottmann, Christian; Dumitrescu, Daniel; Sohns, Christian; Rudolph, Volker; Fox, Henrik
Abstract: Treatment of refractory cardiogenic shock has poor outcome. Levosimendan addition may help to achieve hemodynamic stabilization and improve conditions to where further treatment options such as listing for heart transplantation may become possible. Abstract : Treatment of refractory cardiogenic shock has poor outcome. Levosimendan addition may help to achieve hemodynamic stabilization and improve conditions to where further treatment options such as listing for heart transplantation may become possible.